Faith, Character and Perspective in Judith - Day, Linda (Journal for the study of the Old Testament, 2001)
The purpose of this analysis is to demonstrate the complexity of the religious aspect of the figure of Judith. She is revealed to be a strong, controlling figure, taking initiative throughout all of her actions. Duplicity and violence are also evident in Judith’s actions. Hence, she should not be viewed as a model of piety. This assessment of the book of Judith pays attention to point of view as it is manifested throughout the story, that of the narrator, the other characters and the readers.